Addressing global challenges: How does the integration of rural industries in China enhance agricultural resilience? - Xiaoli Zhou; Mingyang Han (PLoS ONE, 2025)
Promoting the integrated development of rural industries represents a crucial pathway for accelerating the modernization of the entire industrial chain and consolidating and enhancing agricultural resilience. This study constructs provincial-level panel data for China spanning 2012–2022 and employs a multidimensional, visualization-based, and spatial research paradigm to comprehensively examine the impact effects and mechanisms through which rural industrial integration empowers agricultural resilience in China. The findings reveal that, first, rural industrial integration can effectively enhance agricultural resilience levels, with stable economic returns and diversified functional development serving as key pathways for improving agricultural resilience. Second, the eastern and western regions have unleashed agricultural resilience potential through superior policy and environmental advantages, while the relatively homogeneous grain structure and path dependence in the central and northeastern regions have prevented agricultural industrial integration from effectively achieving expected outcomes. Third, structural rationalization has improved resource allocation efficiency, but industrial structure advancement and industrial structure sophistication have actually diminished the enhancement effects on agricultural resilience. Fourth, urbanization has led to adverse resource competition, reducing the positive impact of rural industrial integration on agricultural resilience levels. Fifth, the enhancement of agricultural resilience through rural industrial integration demonstrates geographically-distant resource spillover effects to neighboring regions. This research provides an important theoretical framework and practical paradigm for global agricultural transformation, offering particularly significant strategic guidance for developing countries in building resilient agricultural systems, addressing climate change impacts, and ensuring food security.